VALIDATION OF EDUCATIONAL GAMES IN PHARMACOLOGY - Zepponi, Karla Meira Castro; Aparecida Doretto Braccialli, Luzmarina; Pinheiro, Osni Lazaro [UNESP] (Revista Pesquisa Qualitativa - RPQ, 2021)
Introduction The use of educational technology, through a playful strategy, can facilitate student learning. Objective To build two games to be applied to students of the Pharmacy Technical Course of a Public Education Institution and to validate them by judges in the area of Pharmacology and Education. Method This is a descriptive, observational and qualitative study, with data collection subtracted from the evaluation of four judges from the Pharmacology area and four from the Education area. The games were validated and enriched by filling in observations placed by the judges. These instruments were reorganized, forming nuclei of meaning, fostering a content analysis by thematic modality. Results Two thematic categories were evidenced: Benefits of games in learning and Care with contents and rules in the search for learning through games. Conclusions The notes made by the judges brought a more dynamic and purposeful proposal for learning through games.
VALIDAÇÃO DE JOGOS EDUCATIVOS EM FARMACOLOGIA
Keywords: Game; Learning; Teachin; Teaching Material